PENGARUH LAJU PERTUMBUHAN SEKTOR INDUSTRI SEDANG, INVESTASI DAN UPAH TERHADAP PENYERAPAN TENAGA KERJA KABUPATEN GRESIK TAHUN 2009 - 2014 - yuliaty, hertin; ibdad, izdadul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2017)
ABSTRACKThis research is useful to determine whether there is influence the pace of growth in the industrial sector was, investment and wages that are in Gresik from 2009 to 2014 on employment. It begins with the author's observation on the growth of the industry is, investment and wages within a period of six years, which of course increase and also decrease. From the analysis of the test that the authors prove that the only investment that is positive and significant effect on employment. While the small industrial sector growth and wages is positive but not significant effect on employmentÂ Keyword : Laju Pertumbuhan, Investasi, Upah dan Penyerapan tenaga kerja